PENERAPAN MODEL PEMBELAJARANPROBING PROMPTING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA NEGERI 4 PEKANBARU PEKANBARU - Habibina Nora Tudini; Erviyenni Erviyenni; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purposes of research are to know the improvement of student learning achievement and value of influence by implementing of learning model probing prompting on the structure ofatoms in the class X SMAN 4 Pekanbaru. The from on the study was an experiment with a randomized control group pretest-posttest design. The research sample consisted two class, class X MIPA 4 as experiment class and class X MIPA 3 as control class randomly determined after the normality test using Liliefors testand homogenity test. Instrument in this research is a question of atomic structure that has been test validation and reliability. The Results LKPD of the test is 89,5% and results reliability of the test is 0,937. Hypothesis was done by using test-t right side. Research result shown that the implementation of learning model probing-prompting can improve students learning achievement on the strukture of atoms where tcount=3,14> ttable = 1,66.Key Words : Learning ModelProbing-Prompting, Learning Achievement, Structure of Atomic